COVID-19 disease characteristics in different pediatric age groups - ŞENYÜREK, BETÜL; BORAN, PERRAN; KEPENEKLİ KADAYİFCİ, EDA; YAKUT, NURHAYAT; KARAHASAN, AYŞEGÜL; AYDINER, ELİF; MEMİŞOĞLU, ASLI; GÖKDEMİR, YASEMİN; ERDEM ERALP, ELA; KARADAĞ, BÜLENT TANER (My University, 2022)
Introduction: Little is known about the COVID-19 disease characteristics and differences between different pediatric age groups. This study aimed to investigate the disease characteristics according to age groups. Methodology: We conducted a retrospective, single-center study of pediatric COVID-19 in a tertiary care hospital in Turkey. The patients were divided into three groups: 15 days-24 months old (Group 1), 25-144 months old (Group 2), and 145-210 months old (Group 3) according to age. Results: A total of 139 pediatric patients with COVID-19 were examined. Twenty-nine patients (20.9%) were in Group 1, 52 (37.4%) were in Group 2, 58 (41.7%) were in Group 3. Thirty-nine patients (28.1%) were hospitalized. The most common symptoms were cough (55.4%) and fever (51.8%). The median chest X-ray (CXR) score of hospitalized patients was 1 (min 0-max 7), and the median CXR score of outpatients was 1 (min 0-max 6). Fever was significantly more frequent in Group 1, and chest pain was more frequent in Group 3. Group 1 had significantly higher WBC, lymphocyte, thrombocyte counts, AST, LDH, D-dimer, and Troponin T levels but lower hemoglobin, total protein, and albumin levels. The treatment included antibiotics, oseltamivir, hydroxychloroquine, and supportive therapy. Only one patient (0.7%) received noninvasive mechanical ventilatory support. Conclusions: As we know the clinical course of COVID-19 in children is less severe than in adults. We also found significant differences in both clinical and laboratory findings between different pediatric age groups which supports the theory that disease pathogenesis is highly variable according to age.
Keywords: Yaşam Bilimleri; Temel Bilimler; Life Sciences; Natural Sciences; BULAŞICI HASTALIKLAR; İmmünoloji; Yaşam Bilimleri (LIFE); INFECTIOUS DISEASES; IMMUNOLOGY; Life Sciences (LIFE); General Immunology and Microbiology; Immunology; Infectious Diseases; Health Sciences; Children; COVID-19; pediatric age groups; Turkey; CLINICAL CHARACTERISTICS; CORONAVIRUS; CHILDREN